Occurrence and surveillance of Taiwanese bovine arboviruses using hematophagous insects in dairy farms during 2012–2019 - Tzeng, Hau-You; Ting, Lu-Jen; Chiu, Chin-Ing; Lin, Nien-Nung; Liao, Kuei-Min; Tu, Wu-Chun (Journal of medical entomology, 2023)
Culicoides-borne viruses are an important arbovirus group causing bovine diseases. During 2012–2019, 2,525 pools consisting of 108,937 specimens of vectors were subjected to PCR detection of bovine arbovirus belonging to Orthobunyavirus, Orbivirus, and Ephemerovirus. Twelve virus RNAs, of which 6, that is, Shuni virus, Shamonda virus, and Sathuperi virus in Orthobunyavirus and Sathuvachari virus and epizootic hemorrhagic disease virus serotypes 4 and 7 in Orbivirus were detected for the first time in the area. Potential vector species were evaluated by the minimum infection rate, and the population abundance of Culicoides oxystoma, Culex tritaeniorhynchus, and Anopheles sinensis indicated that they were the main potential vector species in dairy farms inTaiwan.